Novel Characterization of Myeloid-Derived Suppressor Cells in Tumor Microenvironment - Li, Yanan; He, Hongdan; Jihu, Ribu; Zhou, Junfu; Zeng, Rui; Yan, Hengxiu (Frontiers in Cell and Developmental Biology, 2021)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneity group of cells generated in various pathologic conditions, which have been known to be key components of the tumor microenvironment (TME) involving in tumor immune tolerance. So MDSCs have been extensively researched recently. As its name suggests, immunosuppression is the widely accepted function of MDSCs. Aside from suppressing antitumor immune responses, MDSCs in the TME also stimulate tumor angiogenesis and metastasis, thereby promoting tumor growth and development. Therefore, altering the recruitment, expansion, activation, and immunosuppression of MDSCs could partially restore antitumor immunity. So, this review focused on the favorable TME conditions that promote the immunosuppressive effects of MDSCs and contribute to targeted therapies with increased precision for MDSCs.